Demonstrating the In Situ Biodegradation Potential of Phenol Using Bio‐Sep® Bio‐Traps® and Stable Isotope Probing. Issue 1 (18th January 2013) - Williams, Neil; Hyland, Amy; Mitchener, Richard; Sublette, Kerry; Key, Katherine C.; Davis, Greg; Ogles, Dora; Baldwin, Brett; Biernacki, Anita
Abstract The effect of phenol concentration on phenol biodegradation at an industrial site in the south of Wales, United Kingdom, was investigated using standard Bio‐Sep® Bio‐Traps® and Bio‐Traps® coupled with stable isotope probing (SIP). Unlike many 13C‐amendments used in SIP studies (such as hydrocarbons) that physically and reversibly adsorb to the activated carbon component of the Bio‐Sep® beads, phenol is known to irreversibly chemisorb to activated carbon. Bio‐Traps® were deployed for 32 days in nine site groundwater monitoring wells representing a wide range of phenol concentrations. Bio‐Traps® amended with 13C‐phenol were deployed together with non‐amended Bio‐Traps® in three wells. Quantitative polymerase chain reaction (qPCR) analysis of Bio‐Traps® post‐deployment indicated an inhibitory effect of increasing phenol concentration on both total eubacteria and aerobic phenol‐utilizing bacteria as represented by the concentration of phenol hydroxylase gene. Despite the chemisorption of phenol to the Bio‐Sep® beads, activated carbon stable isotope analysis showed incorporation of 13C into biomass and dissolved inorganic carbon (DIC) in each SIP Bio‐Trap® indicating that chemisorbed amendments are bioavailable. However, there was a clear effect of phenol concentration on 13C incorporation in both biomass and DIC confirming phenol inhibition. These results suggest that physical reductions of the phenol concentrations in some areas of the plume will be required before biodegradation of phenol can proceed at a reasonable rate. © 2013 Wiley Periodicals, Inc.